And we dare not write anymore than that which Latin has: Ælfric's Grammar and the history of the simplified description of the English verbal system. (2nd July 2016) - Aaron Smith, K.
Abstract: Linguistic treatments of the Germanic verbal system, including that in English, have presented it as having only two tenses, and thus representing a drastically simplified system in comparison to Indo-European. Such typological characterizations, which have their origins in the comparative traditions of the 18th and 19th centuries, ignore, however, the extensive verbal work done through periphrases in Germanic and English. The typologization of German and English as "two-tensed" continues into modern linguistic theory as well. In this paper, I offer an analysis of Ælfric's 10th-century Grammatical treatise to show that already at the time of the writing of his Grammar, the English verb system was viewed in just such simplified terms, that is, as having just two verb forms—a simple present and a simple past. By comparing the presentation of the English verb in Ælfric's grammar to his own writing practices in which he makes ample use of periphrases, I make the claim that Ælfric's focus on the simple present and simple past was formative of a very early theory of English as a two-tensed, simplified verbal system. Thus, I place Ælfric into a more central position in the history of linguistic thought by showing him to be the first to assert the two-tense definition of English.